Rancangan Visual Flight Rules Corridor di Perum LPPNPI Cabang Tanjung Pinang - Rachman, Muhammad Thirafi; Asih, Pribadi; Sinaga, Togi Adnan (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
This design aims to seek data that existed on Raja Haji Fisabilillah, Tanjungpinang Aerodrome for safety and integrated VFR route mapping with other VFR route on Sumatra and The Islands of Riau. It was found that the visual traffic condition have burdened APP. If TWR takes control, there will be misperception between pilot and TWR. Many terrains, bad weather rages frequently where the visibility reaches under 1 kilometres even 400 metres only. With the existence of VFR Corridor Generation, will guarantee the flight safety and become an implementation from VFR Route intergration all over Sumatra and The Islands of Riau.